Economy, territory, and identity: A Rokkanian analysis of Indigenous self-determination in Canada and Norway. (20th January 2022) - Selle, Per; Wilson, Gary N.
Abstract: Indigenous peoples throughout the circumpolar north have made significant progress in terms of securing self-determination through greater political autonomy. Although such change is important, it must be accompanied by greater economic control aimed at reducing state dependencies. Using an analytical framework developed by Norwegian political scientist, Stein Rokkan, this article explores the interplay between economy, territory, and identity among the Inuit in Canada and the Sámi in Norway. It reveals that the economic destinies of both groups have been profoundly influenced by both domestic and international factors that determine the focus and type of economic development they undertake. While the Inuit have pursued a balance of modern and traditional forms of economic development that is grounded in a regionally based model of self-rule, the Sámi have opted for an economic development model that emphasises traditional economic activities and is supported by Norway's international commitments to the rights of Indigenous peoples.